The in vitro antimycobacterial activities of extracts and isolated compounds from selected plants against mycobacterium smegmatis - Koma, Potsiso Letau (My University, 2023)
Mycobacterium tuberculosis is an intracellular facultative microorganism that belongs to the M. tuberculosis complex and causes tuberculosis (TB) in human beings. TB is a global pandemic which poses a health security as the leading cause of death. This study aimed to determine the antioxidant activity, antibacterial activity, synergistic and cytotoxic effects, isolate and characterise bioactive compounds of five selected medicinal plants (Zanthoxylum capense, Ziziphus mucronata, Rosmarinus officinalis, Ximenia caffra and Rhoicissus tridentata). The leaves of the plants were collected, dried, and extracted using solvents of varying polarities (n-hexane, dichloromethane, acetone, methanol, and water). Methanol extracted the highest mass for Z. capense, Z. mucronata and R. tridentata while water extracted the highest mass for R. officinalis and X. caffra. Preliminary screening of major-phytoconstituents was determined using standard chemical methods and all plants lacked alkaloids. Qualitative phytochemical composition, antioxidant and antimycobacterial activity were determined using Thin Layer Chromatography (TLC). The quantity of phytochemicals and antioxidants was determined using colorimetric assay, while the quantitative antimicrobial activity and synergistic effects of the hexane and acetone extracts were determined using microbroth dilution assay. The anti-inflammatory activity was determined using egg albumin denaturation inhibition assay and the antibiofilm activity was also analysed. Cell viability was determined using the [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] MMT reduction assay. On preliminary screening, the different colours indicated the presence of different compounds. The quantity of phytochemicals showed that R. tridentata had the highest total phenolic and tannin content from its water extracts while the highest total flavonoid content was from the methanol extract of R. officinalis. Qualitative antioxidant activity analysis using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, where the yellow bands against the purple indicated the presence of antioxidant compounds, showed that antioxidant compounds were present in all plants except for Z. capense. It also had the lowest quantified antioxidant compounds. Qualitative antibacterial activity showed that R. officinalis and Z. mucronate had inhibited the growth of M. smegmatis from all extracts except their water extracts. R. officinalis had the highest antibacterial activity as compared to all plants and a synergistic outcome was observed when the n-hexane extracts R. officinalis and Z. capense were combined. All the plants were able to inhibit protein denaturation, even though Z. capense had poor anti-inflammatory activity with percentage inhibition of 42%. The plant extracts had a concentration dependent biofilm activity against M. smegmatis. Cell viability assay revealed that acetone extracts of R. tridentata had the highest percentage cell viability while Z. mucronata and Z. capense had the lowest percentage cell viability. Isolation of bioactive compounds was done using bioassay guided fractionation and the structure of the compounds was characterised using nuclear magnetic resonance spectroscopy. The isolated compounds were 2 chromones with (compound 1 is 5-hydroxyl-2-methyl-7-(propan-2βol)-chromone and compound 2 as 7-acetonyl-5-hydroxy-2-methylchromone) and β-sitosterol compounds. All compounds had antibacterial activity against M. smegmatis, compound 4 had the lowest minimum inhibitory concentration (MIC) of 0.125 mg/mL. The study demonstrated that selected medicinal plants have different phytochemicals that are responsible for antioxidant, antibacterial, anti-inflammatory and antibiofilm activities. Further studies are recommended on Mycobacterium tuberculosis and in vivo studies.
Thesis (M. Sc. (Microbiology)) -- University of Limpopo, 2023
Keywords: Mycobacterium tuberculosis.; Mycobacterium smegmatis.; Tuberculosis.; Medicinal plants.; Compounds.; Mycobacteria -- Ecology; Medicinal plants -- Biotechnology; Mycobacterium tuberculosis